Freedom of the writer and director in the interpretation of the topic of the Holodomor (V. Bark’s "Yellow Prince" and O. Yanchuk "Famine – 33") - Макарадзе, Христина Зурабівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article attempts to compare two sequential statements on the basis of semiotic analysis. One of statements is the novel “Zhovtyy kniaz” by V. Barka and the other one is the film “Famine – 33” by O. Yanchuk, because the film is based on the novel. As a result of the bibliographic review it was clarified that nobody has compared “Zhovtyy kniaz” by V. Barka and “Famine – 33” by O. Yanchuk yet. It was considered the novel and the film as a commucative system with its own language. We have translated the language of cinema and literature into a common language of signs and tried to investigate the extent of producer’s intervention. Also it was given a detailed analysis of motives, symbols, compositions in both of these works. Despite the fact that the film coincides with the novel in key story moments, the film differs from the novel by different accents. For example, director reduced religious symbols, psychology in the film. And on the contrary ideology and revealing pathos increase.